2013
DOI: 10.1111/liv.12221
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia clearance with haemofiltration in adults with liver disease

Abstract: Clinically significant ammonia clearance can be achieved in adult patients with hyperammonaemia utilizing continuous VVHF. Ammonia clearance is closely correlated with ultrafiltration rate. HF was associated with a fall in arterial ammonia concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(102 citation statements)
references
References 29 publications
0
101
0
1
Order By: Relevance
“…However, compared to AKI patients without liver dysfunction, patients with both liver dysfunction and AKI are potentially exposed to higher levels of circulating toxins, such as ammonia and cytokines [5,6]. In such patients, intensive correction of ammonia levels is possible using CRRT, and has been associated with improved survival [7,8]. Furthermore, high volume hemofiltration has been associated with improved survival in children with liver failure [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, compared to AKI patients without liver dysfunction, patients with both liver dysfunction and AKI are potentially exposed to higher levels of circulating toxins, such as ammonia and cytokines [5,6]. In such patients, intensive correction of ammonia levels is possible using CRRT, and has been associated with improved survival [7,8]. Furthermore, high volume hemofiltration has been associated with improved survival in children with liver failure [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…One of the early studies in 1987 that used hemodialysis for treatment of HE showed improvement in the level of consciousness in 59% of the patients [18]. Another prospective controlled study, which included 10 patients with liver failure, showed improvement in SAL with CRRT [1]. So far, the literature in the adult population is limited to case reports and small case series; there has been no large study on the use of RRT for hyperammonemia in liver patients [19].…”
Section: Renal Replacement Therapymentioning
confidence: 99%
“…The absorbed ammonia then enters the liver through portal circulation and is converted to urea. There are also non-hepatic pathways for ammonia clearance (e.g., peripheral conversion to glutamine in muscle tissue) that are beyond the scope of this review [1]. Accumulation of ammonia due to chronic intrinsic liver dysfunction (e.g., cirrhosis) could lead to increased SAL in the systemic circulation, neuronal dysfunction, and hepatic encephalopathy, which is a major cause of mortality in patients with liver failure [2].…”
Section: Pathophysiologic Conceptsmentioning
confidence: 99%
“…Further indications may include the following: removal of toxic substances (eg, acetaminophen, ammonia), difficult to treat hyponatremia, or difficult to treat hyperthermia [50,51]. Continuous modes of RRT are preferred over intermittent ones because the latter have been associated with increased risk of hemodynamic instability and cerebral edema [52].…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…The approach to cerebral edema and intracranial hypertension consists of the following: (1) head of the bed greater than 30°; (2) minimize patient stimulation; (3) sedation and invasive mechanical ventilation; (4) treat fever (although active hypothermia has not been proven to prevent cerebral edema and intracranial hypertension) [56,57]; (5) treat seizures (although prophylaxis has unclear value) [1]; (6) aim for a mean arterial pressure of at least 75 mm Hg with fluids and/or vasopressors, with the goal being to maintain an intracranial pressure less than 25 mm Hg and a cerebral perfusion pressure greater than 50 mm Hg; (7) consider using RRT to promote more effective ammonia clearance [51]; (8) aim for a serum sodium of 145 to 155 mmol/L with hypertonic saline (3%-30% infusion) for prophylaxis in patients with grade III-IV HE [58]; (9) consider using mannitol (0.5-1 g/kg bolus) to transiently reduce intracranial pressure when there is established intracranial hypertension (repeat if serum osmolality b320 mOsm/L) [59]; and (10) consider using hyperventilation (aiming for a PCO 2 25-30 mm Hg) in cases of established intracranial hypertension despite optimized treatment to try to delay the progression to tonsillar herniation [60].…”
Section: Cerebral Edema and Intracranial Hypertensionmentioning
confidence: 99%